Controles y regulaciones para una vitivinicultura incontrolable: la trayectoria de las direcciones general de industrias y de fomento industrial y agrícola (Mendoza, Argentina, 1908-1943) - Rodríguez Vázquez, Florencia (Universidad Nacional del Litoral, 2022)
The study of state management with an impact on agro-industries makes it necessary to stop at the guidelines and directives deployed by public agencies. In the case of regional economies, the design and organization of technical agencies that met the demands of various agro industries takes on special interest to learn about particular directions, the degree of complementarity with national jurisdictions, as well as the constituencies that made them up. From the reconstruction of the Directorate of Industries of the province of Mendoza, a marked specialization of the dependence on wine issues and finally a process of expansion of functions to meet the requirements of an agribusiness in transformation can be seen